Assessing How Fintech Peer-to-Peer Lending, Banking Digitization, and Banking Credit Risk Affect the Financial Performance of Indonesian Commercial Banks KBMI 4 in Digital Era - Prawira, Anggun Wida; Susilowati, Heni; Ratnaningrum, Ratnaningrum (LPPM Universitas Trunojoyo Madura, 2024)
This study aims to determine and analyses the effect of Fintech Peer to Peer Lending, Bank Digitization and Non-Performing Loans on Banking Financial Performance (Return on Asset) at KBMI 4 Commercial Banks in 2019-2023. This type of research is descriptive with quantitative analysis. The object of the research is the audited financial report of Bank Umum KBMI 4 listed on the Indonesia Stock Exchange and the report from the Financial Services Authority. The sample was selected using the Purposive Sampling technique. Data analysis techniques using multiple linear regression analysis. Findings: P2P Lending has a negative and significant effect on Return on Assets. Bank Digitization does not have a positive and significant effect on Return on Assets. Non-Performing Loans have a negative and significant effect on Return on Assets. Peer to Peer Lending, Banking Digitization, Non-Performing Loan simultaneously have a significant effect on Return on Assets. Banks in KBMI Category 4 must carry out Product Innovation to compete with P2P lending. By establishing Partnerships, conducting Market Segment Approaches, developing Digitization: and using big data and analytics. By implementing these strategies, banks remain relevant and competitive in the digital era.